Platform strategies a guidebook for entrepreneurs in the platform economy - Belleflamme, Paul; Neysen, Nicolas (Routledge, 2023)
"Over the past decade, platforms have spread through many industries and generated an increasing share of the global economy. Many of the world's most valuable companies have adopted a platform-based business model and today, we find that platforms pervade our everyday lives. So far, however, the existing management literature has failed to provide professionals and students with appropriate tools to understand the business models that make those platforms successful. This book offers rigorous analysis of the complexity of platforms, as well as practical strategic guidance and tools to help you deal with this complexity. Written in an accessible style and based on a comprehensive approach, Platform Strategies is self-contained and does not require the reader to have specific prior knowledge. The book is both academically rigorous and a pragmatic and efficient guide, incorporating path-breaking insights from academic research on platforms with real-world applications of concepts and tools. The book engages with case studies and highlights important take-aways that can be implemented in practice. You'll learn how to use new tools of strategic management and how to adapt well-established ones. This book is an invaluable resource for entrepreneurs (experienced or aspiring), managers of existing platforms and businesses, professionals, and students in business, management and economics"--